2017
DOI: 10.1002/ppsc.201700302
|View full text |Cite
|
Sign up to set email alerts
|

Needle‐Leaf‐Like Cu2Mo6S8 Films for Highly Efficient Visible‐Light Photocatalysis

Abstract: Ternary sulfide Cu2Mo6S8 films with needle‐leaf‐like structures are grown on copper plates via a facile two‐step route. The needle‐leaf‐like Cu2Mo6S8 structures are directly converted from pregrown Cu(OH)2 nanowires on copper plates via a hydrothermal process. Interestingly, under visible light the hierarchically structured Cu2Mo6S8 films exhibit significantly improved photocatalytic performance in the degradation of methylene blue dye when compared to Cu(OH)2 nanowires. This result is attributed to the larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[ 104 ] This type of ternary metal chalcogenides is a member of the important family called as Chevrel phase and provides promising property such as superconductivity. Up to now, Chevrel phases were employed as cathode material for rechargeable Mg batteries, [ 105 ] electrocatalysts in H 2 evolution reaction, [ 106 ] visible‐light photocatalyst, [ 107 ] etc.…”
Section: Synthesis Of Rmcsmentioning
confidence: 99%
“…[ 104 ] This type of ternary metal chalcogenides is a member of the important family called as Chevrel phase and provides promising property such as superconductivity. Up to now, Chevrel phases were employed as cathode material for rechargeable Mg batteries, [ 105 ] electrocatalysts in H 2 evolution reaction, [ 106 ] visible‐light photocatalyst, [ 107 ] etc.…”
Section: Synthesis Of Rmcsmentioning
confidence: 99%
“…Therefore, it is imperative to develop a new type of high-efficiency photocatalyst to make up for the shortcomings of traditional materials. Recent series of studies have shown that ternary sulfides such as Cu 3 SbS 3 [15], ZnIn 2 S 4 [16], Cu 2 Mo 6 S 8 [17], and CuS x Se 1-x [18] are highly attractive due to their low cost, excellent electrical properties, and nonlinear optical properties. Particularly, their physicochemical properties can be facile regulated by adjusting the composition of each element, making them stand out among many new photocatalysts [19].…”
Section: Introductionmentioning
confidence: 99%